The association between newborn cord blood steroids and ambient prenatal exposure to air pollution: findings from the ENVIRONAGE birth cohort - Michelle Plusquin; Congrong Wang; Charlotte Cosemans; Harry A. Roels; Maartje Vangeneugden; Bruno Lapauw; Tom Fiers; Guy T'Sjoen; Tim S. Nawrot (BMC, 2023)
Abstract Knowledge of whether prenatal exposure to ambient air pollution disrupts steroidogenesis is currently lacking. We investigated the association between prenatal ambient air pollution and highly accurate measurements of cord blood steroid hormones from the androgenic pathway. This study included 397 newborns born between the years 2010 and 2015 from the ENVIRONAGE cohort in Belgium of whom six cord blood steroid levels were measured: 17α-hydroxypregnenolone, 17α-hydroxyprogesterone, dehydroepiandrosterone, pregnenolone, androstenedione, and testosterone. Maternal ambient exposure to PM2.5 (particles with aerodynamic diameter ≤ 2.5 μm), NO2, and black carbon (BC) were estimated daily during the entire pregnancy using a high-resolution spatiotemporal model. The associations between the cord blood steroids and the air pollutants were tested and estimated by first fitting linear regression models and followed by fitting weekly prenatal exposures to distributed lag models (DLM). These analyses accounted for possible confounders, coexposures, and an interaction effect between sex and the exposure. We examined mixture effects and critical exposure windows of PM2.5, NO2 and BC on cord blood steroids via the Bayesian kernel machine regression distributed lag model (BKMR-DLM). An interquartile range (IQR) increment of 7.96 µg/m3 in PM2.5 exposure during pregnancy trimester 3 was associated with an increase of 23.01% (99% confidence interval: 3.26-46.54%) in cord blood levels of 17α-hydroxypregnenolone, and an IQR increment of 0.58 µg/m³ in BC exposure during trimester 1 was associated with a decrease of 11.00% (99% CI: -19.86 to -0.012%) in cord blood levels of androstenedione. For these two models, the DLM statistics identified sensitive gestational time windows for cord blood steroids and ambient air pollution exposures, in particular for 17α-hydroxypregnenolone and PM2.5 exposure during trimester 3 (weeks 28-36) and for androsterone and BC exposure during early pregnancy (weeks 2-13) as well as during mid-pregnancy (weeks 18-26). We identified interaction effects between pollutants, which has been suggested especially for NO2. Our results suggest that prenatal exposure to ambient air pollutants during pregnancy interferes with steroid levels in cord blood. Further studies should investigate potential early-life action mechanisms and possible later-in-life adverse effects of hormonal disturbances due to air pollution exposure.